Development of high-performance flexible solid state supercapacitor based on activated carbon and electrospun TiO2 nanofibers. (May 2015) - Kolathodi, Muhamed Shareef; Natarajan, Tirupattur Srinivasan
Graphical abstract: Abstract : Here we report a solid state flexible supercapacitor based on high surface area activated carbon and electrospun nanofibers of anatase phase titanium dioxide. The granular and high aspect ratio nanofibers were synthesized by sol–gel assisted electrospinning followed by calcination. Flexible and transparent thin film prepared from polyvinyl alcohol and phosphoric acid was used as electrolyte cum separator for the supercapacitor. The flexible supercapacitor achieved high specific capacitance of 310 F/g with higher energy density and excellent rate capability.